Antarktis: inlandsis, shelf-is och stigande havsnivå - Darelius, Elin (Naturen, 2014)
I klimatsammanhang har strålkastarljuset länge varit riktade mot de känsliga polarområdena och smältande is. Bilder på isbjörnar som klamrar sig fast vid ett ensamt isflak figurerar varje höst i media när årets – ofta rekordlåga – minimum i utbredning av Arktisk havsis offentliggörs. Men nyligen har is-överskrifterna allt oftare kommit söderifrån, de har handlat om Antarktis, om shelf-is som smälter, om en stigande havsnivå och om möjligheten för att inlandsisen i Väst-Antarktis ska kollapsa.
Keywords: Sørishavet; brehylle; havnivåstigning; innlandsis; isbrem; isshelf; klimaendringer

Exceptionally Warm and Prolonged Flow of Warm Deep Water Toward the Filchner-Ronne Ice Shelf in 2017 - Ryan, Svenja; Hellmer, Hartmut H; Janout, Markus; Darelius, Elin; Vignes, Lucie; Schröder, Michael (Geophysical Research Letters, 2020)
The Filchner-Ronne Ice Shelf, fringing the southern Weddell Sea, is Antarctica's second largest ice shelf. At present, basal melt rates are low due to active dense water formation; however, model projections suggest a drastic increase in the future due to enhanced inflow of open-ocean warm water. Mooring observations from 2014 to 2016 along the eastern flank of the Filchner Trough (76°S) revealed a distinct seasonal cycle with inflow if Warm Deep Water during summer and autumn. Here we present extended time series showing an exceptionally warm and long inflow in 2017, with maximum temperatures exceeding 0.5°C. Warm temperatures persisted throughout winter, associated with a fresh anomaly, which lead to a change in stratification over the shelf, favoring an earlier inflow in the following summer. We suggest that the fresh anomaly developed upstream after anomalous summer sea ice melting and contributed to a shoaling of the shelf break thermocline.
Keywords: Sørishavet; Weddellhavet; batymetri; brehylle; geofysikk; havis; isbrem; kontinentalsokkel; oseanografi; sjøis; smelting

Warm Circumpolar Deep Water at the Western Getz Ice Shelf Front, Antarctica - Assmann, Karen; Darelius, Elin Maria K; Wåhlin, Anna K; Kim, Tae Wan; Lee, Sang Hoon (Geophysical Research Letters, 2019)
The Getz Ice Shelf is one of the largest sources of fresh water from ice shelf basal melt in Antarctica. We present new observations from three moorings west of Siple Island 2016–2018. All moorings show a persistent flow of modified Circumpolar Deep Water toward the western Getz Ice Shelf. Unmodified Circumpolar Deep Water with temperatures up to 1.5 °C reaches the ice shelf front in frequent episodes. These represent the warmest water observed at any ice shelf front in the Amundsen Sea. Mean currents within the warm bottom layer of 18–20 cm/s imply an advection time scale of 7 days from shelf break to ice shelf front. Zonal wind stress at the shelf break affects heat content at the ice shelf front on weekly to monthly time scales. Our 2-year mooring records also evince that upwelling over the shelf break controls thermocline depth on subannual to annual time scales.
Keywords: Antarktis; geofysikk; glasiologi; isbrem; isshelf; observasjoner

Necessary Conditions for Warm Inflow Toward the Filchner Ice Shelf, Weddell Sea - Daae, Kjersti; Hattermann, Tore; Darelius, Elin Maria K; Mueller, Rachael D; Naughten, Kaitlin A; Timmermann, Ralph; Hellmer, Hartmut H (Geophysical Research Letters, 2020)
Understanding changes in Antarctic ice shelf basal melting is a major challenge for predicting future sea level. Currently, warm Circumpolar Deep Water surrounding Antarctica has limited access to the Weddell Sea continental shelf; consequently, melt rates at Filchner-Ronne Ice Shelf are low. However, large-scale model projections suggest that changes to the Antarctic Slope Front and the coastal circulation may enhance warm inflows within this century. We use a regional high-resolution ice shelf cavity and ocean circulation model to explore forcing changes that may trigger this regime shift. Our results suggest two necessary conditions for supporting a sustained warm inflow into the Filchner Ice Shelf cavity: (i) an extreme relaxation of the Antarctic Slope Front density gradient and (ii) substantial freshening of the dense shelf water. We also find that the on-shelf transport over the western Weddell Sea shelf is sensitive to the Filchner Trough overflow characteristics.
Keywords: Sørishavet; Weddellhavet; glasiologi; havnivåstigning; innlandsis; isbrem; isshelf; klimaendringer